“Funny Weapons”: The Norms of Humour in the Construction of Far‐Right Political Polarisation - Gabriel Bayarri Toscano; Concepción Fernández-Villanueva (Social Inclusion)
Jair Bolsonaro in Brazil, Nayib Bukele in El Salvador, and Javier Milei in Argentina are just a few paradigmatic cases that represent, to different degrees, the rise of populism, the advances of right‐wing radicalism, and the resurgence of extreme nationalism in Latin America in the last decade. The question that arose after the victory of the far‐right was: How could this have happened? One of the instruments that undoubtedly contributed to this unexpected victory was a peculiar aspect of these political campaigns: memetic communication. Through the use of memes in social media (above all WhatsApp), the far‐right transformed violent discourses against political opponents, feminism, racialised persons, and poverty into a series of messages legitimised through humour and irony. This process operated as a simplification that disrupted stable systems of social norms and metaphorical frameworks. Between September 2022 and February 2024, in the weeks leading up to and following each presidential election, we collected and analysed visual data employing open‐source software. We also conducted ethnographic fieldwork and digital ethnography during the weeks preceding the elections to capture online and offline discourses and the affective milieu of each electoral campaign, providing contextual insight into the impact of memetic communication. Our analysis demonstrates the trivialisation and legitimisation of violence against political opponents and other social groups. This process may also be interpreted as an attempt to render the unconstitutional as legitimate, framing exclusionary or violent political acts as necessary or even virtuous. Much of this legitimisation was camouflaged under the mask of supposed humour and irony, which in reality was insulting, prejudicial, and dehumanising.